The value of 'expert trainees' in primary care postgraduate education. Issue 4 (3rd July 2020) - Thurston, Emma; Forde, Emer; Wedderburn, Clare
ABSTRACT: Peer-led teaching is well established within many undergraduate medical courses but relatively underutilised in postgraduate training, despite the fact it can be useful for both teachers and learners. A significant number of doctors training to be GPs bring expertise and experience from other specialities and in this paper we explore the potential of using 'expert trainees' to teach their peers on postgraduate GP training programmes. A GP trainee with expertise in Lifestyle Medicine taught alongside local and national experts and delivered workshops to her peers. Questionnaires were used to establish the acceptability and quality of 'expert trainee' peer-led education. This was a positive experience for the 'expert trainee' who felt valued both as a trainee and as someone with expert knowledge, and for her peers with excellent feedback on her workshop. The knowledge and skills of 'expert trainees' represent an untapped resource which could be more systematically and effectively used within GP education.